Local e government in the United States: Transformation or incremental change? - Norris, Donald F.; Reddick, Christopher G. (2013)
In this article, the authors address the recent trajectory of local e-government in the United States and compare it with the predictions of early e-government writings, using empirical data from two nationwide surveys of e-government among American local governments. The authors find that local e-government has not produced the results that those writings predicted. Instead, its development has largely been incremental, and local e-government is mainly about delivering information and services online, followed by a few transactions and limited interactivity. Local e-government is also mainly one way, from government to citizens, and there is little or no evidence that it is transformative in any way. This disparity between early predictions and actual results is partly attributable to the incremental nature of American public administration. Other reasons include a lack of attention by early writers to the history of information technology in government and the influence of technological determinism on those writings. - Reproduced.
Keywords: E governance